A review and comparison of ontology-based approaches to robot autonomy. (2019) - Olivares-Alarcos, Alberto; Beßler, Daniel; Khamis, Alaa; Goncalves, Paulo; Habib, Maki K.; Bermejo-Alonso, Julita; Barreto, Marcos; Diab, Mohammed; Rosell, Jan; Quintas, João; Olszewska, Joanna; Nakawala, Hirenkumar; et al.
Abstract: Within the next decades, robots will need to be able to execute a large variety of tasks autonomously in a large variety of environments. To relax the resulting programming effort, a knowledge-enabled approach to robot programming can be adopted to organize information in re-usable knowledge pieces. However, for the ease of reuse, there needs to be an agreement on the meaning of terms. A common approach is to represent these terms using ontology languages that conceptualize the respective domain. In this work, we will review projects that use ontologies to support robot autonomy. We will systematically search for projects that fulfill a set of inclusion criteria and compare them with each other with respect to the scope of their ontology, what types of cognitive capabilities are supported by the use of ontologies, and which is their application domain.